Postawy twórcze dzieci w młodszym wieku szkolnym – tendencje zmian - Ewa Wysocka; Jolanta Pułka (Problemy Wczesnej Edukacji)
In the article, the authors put forward and develop a thesis on the regression of creative attitudes in the course of school education. The process of developing creative attitudes among children is analyzed in the perspective of the role and objectives of school education. The authors examine the level and dynamics of the development of creative attitudes in the course of school education (the first 3 years of early school teaching). Creative attitudes include: divergent thinking, creative motivation, and strategies of coping with difficult tasks (intrapersonal and interpersonal strategies). The research was conducted on a representative nationwide sample. The data gathered as a result of this research point to a low level of creative attitudes among early school children, and their negative development in the course of school education.